INFORMATION AND COMMUNICATION TECHNOLOGIES (ICT) IN ONLINE LEARNING MEDIA - Yeni Tri Nur Rahmawati; Suheri Suheri (FORPIM PTKIS ZONA TAPAL KUDA, 2023)
The development of ICT, especially the development of computer technology that switched from desktops to mobile devices is so fast and makes people able to work dynamically without having to sit for hours in front of the computer. Evidently, according to a Nielsen report, more than 65 percent of Indonesians work and access social networks via mobile devices. The rapid development of mobile technology brings development to mobile apps that are also growing. Even mobile application technology has touched the world of education. Information technology includes all matters related to processes, use as tools, manipulation, and management of information. While communication technology is everything related to the use of tools to process and transfer data from one device to another. Zoom is one of the effective learning media during the pandemic and can be used in the next process when schools close their students during the active learning process.